Comprehensive toxicity assessment of silver nanoparticles on Bacteria, human vein endothelial cells, and Caenorhabditis Elegans - Bircan Dinç (Results in Chemistry)
Silver nanoparticles (AgNPs) exhibit concentration-dependent toxicity across multiple biological systems. In this study, it was investigated the effects of AgNPs on bacteria (Escherichia coli and Bacillus subtilis), a model organism (Caenorhabditis elegans), and human vein endothelial cells (HUVECs) at low concentrations (10, 30, and 50 μg/mL).The AgNPs were synthesized using a chemical reduction method and thoroughly characterized, showing a hydrodynamic size of 55 nm, a zeta potential of −57 mV, and thermal decomposition temperatures ranging from 182 to 318 °C. Our results revealed a significant inhibition of bacterial growth (52 % at 50 μg/mL), a 25 % reduction in C. elegans reproduction at just 10 μg/mL, and a decrease in body bending frequency from 42 to 19 beats per minute. In HUVEC cells, the IC50 was found to be 38 μg/mL, with cellular uptake increasing proportionally to concentration after 48 h.This study highlights the unique toxicological profile of AgNPs at low concentrations across multiple biological systems, emphasizing the importance of careful consideration for their safe use in biomedical and environmental applications.